Organization of neural systems expressing melanocortin‐3 receptors in the mouse brain: Evidence for sexual dimorphism. Issue 16 (30th June 2022) - Bedenbaugh, Michelle N.; Brener, Samantha C.; Maldonado, Jose; Lippert, Rachel N.; Sweeney, Patrick; Cone, Roger D.; Simerly, Richard B.
Abstract: The central melanocortin system is fundamentally important for controlling food intake and energy homeostasis. Melanocortin‐3 receptor (MC3R) is one of two major receptors of the melanocortin system found in the brain. In contrast to the well‐characterized melanocortin‐4 receptor (MC4R), little is known regarding the organization of MC3R‐expressing neural circuits. To increase our understanding of the intrinsic organization of MC3R neural circuits, identify specific differences between males and females, and gain a neural systems level perspective of this circuitry, we conducted a brain‐wide mapping of neurons labeled for MC3R and characterized the distribution of their projections. Analysis revealed MC3R neuronal and terminal labeling in multiple brain regions that control a diverse range of physiological functions and behavioral processes. Notably, dense labeling was observed in the hypothalamus, as well as areas that share considerable connections with the hypothalamus, including the cortex, amygdala, thalamus, and brainstem. Additionally, MC3R neuronal labeling was sexually dimorphic in several areas, including the anteroventral periventricular area, arcuate nucleus, principal nucleus of the bed nucleus of the stria terminalis, and ventral premammillary region. Altogether, anatomical evidence reported here suggests that MC3R has the potential to influence several different classes of motivated behavior that are essential for survival, including ingestive, reproductive, defensive, and arousal behaviors, and is likely to modulate these behaviors differently in males and females.